Detecting people's and landscape's identity in a changing mountain landscape. An example from the northern Apennines. (16th November 2016) - Dossche, Rebekka; Rogge, Elke; Van Eetvelde, Veerle
Abstract: Mountain areas in the northern Apennines (Italy) were historically characterised by rural landscapes. Since the 1950s, rapid and widespread land abandonment caused large transformations in the landscape that resulted in a landscape identity crisis. Currently, many people continue to identify and associate themselves with a landscape that no longer exists, whilst others identify themselves with a future landscape that as yet does not exist. This paper explores the concept of landscape identity through empirical research based on a series of in-depth interviews, examination of the contextualised conspicuous spatial and temporal changes and consideration of individual and collective identities. Therefore, firstly, factors influencing the changes in landscape identity through time are identified and, secondly, so-called 'tipping points' and their consequential impacts on landscape identity loss or change are detected. Finally, it is the intention of this article to explore and discover the ways in which the concept of landscape identity can be approached and employed in a continuously changing environment.